The environmental effectiveness of alternative agri-environmental policy reforms: theoretical and empirical analysis - Lankoski, Jussi; Ollikainen, Markku (Agricultural Research Centre of Finland, 1999)
Artikkelissa analysoidaan vaihtoehtoisten maatalouden ympäristöpolitiikan reformien tehokkuutta ravinnepäästöjen vähentämisessä, kun ohjauskeinoina voidaan käyttää tuottajahintatukea, lannoiteveroa, suojavyöhyketukea ja suoraa hehtaaritukea. Ympäristötavoitteiden saavuttamiseksi iranomaisen oletetaan sopeuttavan verojen ja tukien muutokset suhteessa toisiinsa niin, että viljelijän voitto ennen sopeutumista pysyy vakiona. Tämä politiikkamuutos johtaa ympäristön kannalta parempaan panoskäyttöön ja sitä kautta ympäristöystävällisempään tuotantoon. Analysoitavat neljä politiikkareformia ovat: tuottajahinnan tai suoran hehtaarituen vähentäminen, mikä korvataan viljelijälle lisäämällä suojavyöhyketukea, ja lannoiteveron lisääminen mikä korvataan viljelijälle lisäämällä joko suoraa tukea tai suojavyöhyketukea. Kaikki reformit vähentävät ravinnepäästöjä, mutta suurin päästöjen vähennys saadaan aikaan lannoiteveron ja suojavyöhyketuen yhdistelmällä. Simuloinnin tulokset osoittavat, että ravinnepäästöjen 30 % vähennys pienentää keskimääräisen viljelijän voittoa aikissa politiikkareformeissa, kun viljelijä on uudelleen optimoinut panoskäyttönsä vastaamaan verojen ja tukien uusia tasoja, ellei tuottajahinnan anneta nousta vähentyneen tuotannon johdosta. Lannoiteveron kompensoiminen suoralla hehtaarituella aiheuttaa pienimmän vähennyksen viljelijän voittoon.

This paper analyzes alternative agri-environmental policy reforms to reduce nutrient runoff when the government has price support, fertilizer tax, buffer zone subsidy and acreage subsidy as available instruments. To promote environmental goals, the government is assumed to adjust the tax and subsidyrates so as to keep the farmer s profits constant. This instrument switch reduces the prices of less-polluting inputs and the farmer re-optimizes his production so that it becomes more environmentally friendly. The four alternative reforms under study are the following: a reduction of the producer price support or acreage subsidy compensated for by a higher buffer zone subsidy, and an increase in the fertilizer tax which is compensated for by either a higher acreage subsidy or a buffer zone subsidy. We show theoretically that although all reforms reduce the nutrient runoff, the last one is the most efficient. Our simulations show that at a 30 % abatement level of nitrogen runoffs all policy mixes decrease the average farmer s profits after the re-adjustment, if the end price is not allowed to in-crease due to decreased production. The smallest loss in the farmer s profits results from a policy mix which compensates for the higher fertilizer tax by a higher acreage subsidy.
Special issue. To mark the 90th anniversary of the scientific agricultural society of Finland
Keywords: typpivalunta; lannoitevero; pinta-ala; puskuri; suojavyöhyke; ravinnepäästöt; acreage subsidy; egri-environmental policy; buffer zone; fertilizer tax; nitrogen runoff